2013
DOI: 10.1039/c2ta01018f
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature synthesis and SERS application of silver molybdenum oxides

Abstract: nanomaterials are synthesized at relatively low temperature (80 C) and with a short hydrothermal treatment time (3 h) using glucose (Glc) as a catalyst. Contrary to previous studies, it is possible to synthesize one of the Ag x Mo y O z binaries at 80 C by altering the pH of the reaction media in the presence of glucose. In addition, further experiments indicate that Ag/h-MoO 3 , Ag 2 Mo 2 O 7 and Ag/b-MoO 3 can be convertedto Ag/a-MoO 3 which can also be synthesized from a reaction involving ammonium heptamol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…[13][14][15][16][17] Recently, hybridization of nanoparticles of noble metals, e.g., Ag, Au, Cu and Pt with semiconductor, structured carbon and magnetic nanomaterials has drawn attention because of their outstanding SERS performance. [18][19][20][21][22][23][24][25][26] Because the optical band gap plays a crucial role in SERS, therefore, the tuning of the absorption band by doping, change in size, etc. is significance for SERS.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Recently, hybridization of nanoparticles of noble metals, e.g., Ag, Au, Cu and Pt with semiconductor, structured carbon and magnetic nanomaterials has drawn attention because of their outstanding SERS performance. [18][19][20][21][22][23][24][25][26] Because the optical band gap plays a crucial role in SERS, therefore, the tuning of the absorption band by doping, change in size, etc. is significance for SERS.…”
Section: Introductionmentioning
confidence: 99%
“…More hotspots in terms of absolute numbers being available in a 3D space will certainly help to transform SERS into a practical analytical technique. To address the issues on 3D geometry of hotspots, various surfactants, DNA, peptide, DNA origami [10], amphiphilic polymers, or even proteins have been used to construct 'fixed' hotspots on solid substrates by preparing oriented assemblies of functional NPs, such as SHINERS [11], core-shell monomers [12], dimers [13,14], trimers [15], chains [16], arrays [17,18], aggregates [19,20], or even multilevel structures [21,22]. On the other side, 'flexible' designs utilizing electronic, ferroelectric, thermal, mechanical strain, or capillary effects have allowed for the tunability of 3D plasmonic hotspots.…”
mentioning
confidence: 99%
“…Singh et al 11 investigated the influence of pH on the formation of broom-and flowerlike Ag 2 MoO 4 heterostructures by the CH approach. In another report, Fodjo et al 25 used the borohydride reduction reaction to prepare Ag 2 MoO 4 nanoparticles for applications in surface-enhanced Raman scattering activities. Also, published studies 12,26 have shown that Ag−Ag 2 MoO 4 composites exhibit good photocatalytic activity under visiblelight irradiation for the degradation of Rhodamine B as well as graphite/Ag 2 MoO 4 lubricants in Ni-based composites to improve tribological properties, preventing the high-friction and wear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, morphological aspects are able to dislocate crystal lattice planes as well as adjacent particles in aggregates, producing defects in the crystals. In another study, 25 the PL properties of Ag 2 MoO 4 crystals were attributed to chargetransfer transitions in the anion molecular complex. However, in our previous research 57 …”
mentioning
confidence: 99%